Characteristics of Station‐Derived Convective Cold Pools Over Equatorial Africa - Jannik Hoeller; Jan O. Haerter; Nicolas A. DaSilva (Geophysical Research Letters)
Abstract Due to their potential role in organizing tropical mesoscale convective systems, a better understanding of cold pool (CP) dynamics in such regions is critical, particularly over land where the diurnal cycle further concentrates convective activity. Numerical models help disentangle the processes involved but often lack observational benchmarks. To close this gap, we analyze nearly 43 years of five‐minute resolution near‐surface timeseries, recorded from 12 automatic weather stations across equatorial Africa during 2019–2023. We identify 4,218 CPs based on criteria for temperature and wind. The identified CP gust fronts, which exhibit respective median temperature and specific humidity decreases of 5.3 K and 2.8 g kg−1, closely correlate with satellite‐observed brightness temperature discontinuities. Despite weak diurnal variation in precipitation, observed CP occurrence shows a pronounced diurnal cycle with an afternoon peak — a feature we attribute to low‐level moisture conditions. Our findings can serve as observational benchmark to improve simulations of CP organization.